Economic analysis of Deuterodon iguape cultured in Nile tilapia ponds - Fernando Henrique GONÇALVES; Newton José Rodrigues da SILVA; Marcelo Barbosa HENRIQUES (Boletim do Instituto de Pesca)
Polyculture systems can promote greater economic efficiency with decreased use of inputs, making the activity more sustainable. The aim of this study was to evaluate the economic feasibility to grow-out lambari (Deuterodon iguape) in cages installed in Nile tilapia (Oreochromis niloticus) ponds. We calculated operational costs and determined the Internal Rate of Return (IRR), Net Present Value (NPV) and the Pay Back Period (PBP) to assess the economic viability of the investment. In a ten-year horizon, the largest positive NPV obtained was $ 83,082.55 for the sale price of $ 0.09 unit-1 of lambari and $ 2.11 kg-1 of Nile tilapia. Under these conditions, the IRR was 61% and PBP was 1.58 years, considered a low risk result due to the speed of the return on invested capital. A simulation of increase the prices of commercial diets shows that the polyculture system can be economic unfeasible if the farmer cannot access the market of live baits for lambari. The polyculture system is economic feasible, even assuming an annual loss of production, considering selling lambari as live baits.